Influencia de la dislexia en la comprensión lectora en los estudiantes de cuarto año de educación básica de la Escuela "Sofia Alarcón de Espín" Parroquia Caracol del cantón Babahoyo, Provincia de Los Ríos - Chica Chica, Nancy Yuliana (2019)
The problems that arise in the students during the teaching-learning process are many, however the most notorious or most important are those related to learning, dyslexia, dyscalculia, digraphy, all very frequent in school activities and that they cause more than a nuisance to students, parents and teachers. Reading comprehension is another of the educational objectives that are commonly truncated and have a slow development process that prevents learning from being fulfilled at certain times, in this way and considering that dyslexia is one of the problems that prevent it from being develop reading and reading comprehension in students, in this research work we intend to study the influence of dyslexia in the reading comprehension of the students of the fourth year of basic education of the school "Sofía Alarcón de Espín" parish Caracol from the canton Babahoyo, province of Los Ríos. For the development of this research work the non-experimental design, the documentary and field modality were used, in the type of research the descriptive, explanatory and exploratory type, the inductive and deductive methods were applied, to a population of 39 people distributed among 37 parents, 1 teacher and 1 institutional leader, obtaining as a result that if there are students with dyslexia problems, that these students with dyslexia make reading and reading comprehension difficult and that there are few activities used to solve this problem. problematic, making the following theoretical proposal of solution Didactic guide of early diagnosis and primary treatment of the problems dyslexia that the students present